Bacteria from wastewater: potential producers of polyhydroxyalkanoates in Vilnius, Lithuania - Tumaševičiūtė, Rasa; Ignatavičius, Gytautas (International Conference “Environmental Engineering”, 2023)
Polymers are currently used as a major raw material in industry, but they are quickly discharged into the environment and cause significant pollution. To tackle this environmental pollution problem, particular attention is being funded to biodegradable polymers, namely polyhydroxyalkanoates (PHAs) produced by microorganisms. This research detects PHA-producing bacteria from the Vilnius City municipal wastewater treatment plant. We confirmed 5 PHA-positive strains belonging to the following genera: Brachymonas, Aeromonas, Enterobacter, Pseudomonas. One of the isolates, Aeromonas media, is a promising strain to produce PHAs with production values ranging up to 0.544 g/L. Bacteria producing more than 0.300 g/L are considered useful for the industrial production of bioplastics. We recommend large-scale studies on this strain to assess their use in the industrial production of biopolymers to develop highimpact bioconversion processes of industrial relevance.